Mobility: Rights, obligations and equity in an ageing society - Ann Frye (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Demographic trends worldwide indicate significant increases in the number of older people in the population in the coming years. There is a close link between age and disability, and the longer people live the more likely they are to become disabled to some degree. Disability takes many forms: physical, sensory and cognitive and all potentially affect people's ability to go out and about independently.
Keywords: 330